DETECTION OF SPIRORCHIID OVA IN BLOOD SAMPLES FROM GREEN SEA TURTLES BY REALTIME POLYMERASE CHAIN REACTION - Ida Ayu Dian Kusuma Dewi (Fakultas Kedokteran Hewan Universitas Udayana, 2025)
Parasite infection has become one of many important pathological conditions contributing to high morbidity and chronic debilitating disease in green sea turtles (Chelonia mydas). Of many identified parasites in green turtles, spirorchiid flukes are one of the most frequent groups identified from stranding cases worldwide with relatively high morbidity ranging from 75%-98%. This study aimed to perform molecular assays on blood samples using filtered blood to concentrate the parasite DNA contained in the circulating ova. A total of nine blood samples were collected during the study; one from a captive green turtle with suspect positive spirorchiidiosis, and eight from wild turtles caught around the Moreton Bay area. The blood filtration resulted in a remarkably low DNA quantity and poor quality which later lead to a lack of positives on PCR assay. The DNA yield from unfiltered blood samples (68.2–374.3 ng/µL; mean = 16.7 ± 110.0 ng/µL) was significantly higher than that from filtered samples (0.95–7.92 ng/µL; mean = 8.02 ± 8.00 ng/µL). Additionally, DNA purity based on the 260/280 ratio was more consistent in unfiltered samples (1.64–2.13; mean = 1.94 ± 0.13), while filtered samples showed highly variable and unreliable purity values (-7.04 to 84.67; mean = 9.19 ± 28.5). The low quality and quantity of DNA may be caused by the parasite’s life stage, which affects the level of infection and parasite load in the host, as well as DNA denaturation during the extraction process using the bead-beating method. Future research should focus on optimizing DNA extraction methods, particularly the duration of bead-beating and the use of effective buffers like sorbitol or SDS. Additionally, regular administration of anthelmintic treatment is recommended in clinical settings to help control Spirorchiid infections in green turtles.